(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2013)
All of us are consumers and we consume things of daily use which we consume and buy according to our needs, preferences and buying power. Consumer behaviour can be defined as the decision-making process and physical activity involved in acquiring, evaluating, using and disposing of goods and services. Consumer companies thus realizing that the Indian consumer market is a tough nut to crack but the one they can’t do without. Consumer behavior is the study of when, why, how, and where people do or do not buy a product. It blends elements from psychology, sociology, social anthropology and economics. The emerging market is used to evaluate the socio economic scenario of the country in terms of the growth of the market and industrial development. The Indian consumer market has never had it better. Higher disposable incomes, the development of modern urban lifestyles and an increase in consumer awareness have affected buyer behaviour — in cities, towns and even rural areas. On the other hand we said that the main factors behind this booming emerging market are the economic liberalization and the perfect competition market, the high standard of living and per capita income, the development of medical facilities and infrastructure, the increase in foreign investments etc. Due to the favourable emerging market, more and more industries are being set up and the customer base is also increasing. Currently, India is the 4th largest economic system in the world in terms of the purchasing power parity. The recent economic development has also put a positive impact on the various sectors. There are too many question floating in the air, the major ones are what the reasons of changes in Consumer Buying Behaviour are? How the Indian Consumer Market change from pyramid to sparkling diamond? What type of Emerging Market the companies dealing with? This primary data based research paper is an attempt to answer the above major questions and present the linkage between consumer preferences and the impact of change in the buying patterns of the consumers. The starting point of the study is to analyse the changing conditions of the products in Indian Market and this study will also be useful to bridge the gap between theory and practice and will provide valuable insight to the managers involved in Marketing and Selling of products and services in Indian Market.